Revisiting phage therapy: new applications for old resources - Nóbrega, Franklin Luzia (2015)
The success of phage therapy is dependent on the development of strategies able to overcome the limitations of bacteriophages as therapeutic agents, the creation of an adequate regulatory framework, the implementation of safety protocols, and the acceptance by the general public. Many approaches have been proposed to circumvent phages intrinsic limitations but none have proved to be completely satisfactory. In this review we present the major hurdles of phage therapy and the solutions proposed to circumvent them. A thorough discussion on the advantages and drawbacks of these solutions is provided and special attention is given to genetic modification of phages as an achievable strategy to shape bacteriophages to exhibit desirable biological properties.